Current Status and Contents of Forest Science Education in Japan: Case Study among Undergraduate Universities - Inoue, Mariko; Joko, Natsuko; Sugiura, Katsuaki; Oishi, Yasuhiko (Journal of the Japanese Forest Society, 2020)
Education reforms changed forest science in universities education in Japanese universities during the 1990's, particularly after a terminological shift from “forestry” to “forest” science. To understand the current status and educational contents, two surveys were conducted using 2018 educational curriculums. The first survey conducted among all universities showed that there were no regulations of education content except for establishment of experimental forests. Various curriculums were found in the courses. Forest education science courses were placed in 29 universities; 25 universities placed the courses in departments previously named "forestry", and four in agriculture or environmental science. Courses names showed 60％ of them to be forest-related and 40％ did not, thus students could not easily identify forest science courses unless they fully read the course syllabus. The second survey that narrowed down using Utsunomiya University, Nihon University and Tokyo University of Agriculture, showed that subjects that included forest science were 199 in total, of which 26 to 53％ were compulsory subjects. Comparing the three universities, only half of the subjects had commonality. Other than the general basics, forest science contents were divided into 10 categories (tree physiology, ecology, silviculture and pedogenesis, insects and animals related to control, disaster prevention and hydrology, engineering, management, policy, contents involved in culture, and wood science). The study shows that forest science education has diversified. Further study is needed to define the content of current courses in greater detail.